2021
DOI: 10.1002/acr.24489
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in Systemic Rheumatic Disease Medications: Patients’ Perspectives During the Height of the COVID‐19 Pandemic in New York City

Abstract: Objective Concerns about severe acute respiratory syndrome coronavirus 2 (SARS–CoV‐2) infection may have led to changes or discontinuation of immunosuppressive medications among patients with systemic rheumatic disease. Our goal was to assess patients’ perspectives regarding medication modifications and deviations from planned uses during the height of the pandemic. Methods Adult patients of 13 rheumatologists at an academic center with physician‐diagnosed rheumatic disease and prescribed disease‐modifying med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Reductions in DMARD use have been reported in other studies 17 19–22. Our results regarding 2020 suggest marked changes compared with 2019 (decreasing starts and increasing stops of bDMARDs/tsDMARDs); such changes in dispensations could be affected by treatment hoarding or prioritisation of use for COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…Reductions in DMARD use have been reported in other studies 17 19–22. Our results regarding 2020 suggest marked changes compared with 2019 (decreasing starts and increasing stops of bDMARDs/tsDMARDs); such changes in dispensations could be affected by treatment hoarding or prioritisation of use for COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…Conversely, those who used the UC model exclusively, and those who transited between the models during the follow-up period had a significant adherence decrease measured through MGLS. Mancuso et al [ 42 ], showed that some medication modifications were suboptimal for disease control in rheumatological patients, but were made to mitigate infection risk and minimize potential harm when cessation of in-person office visits made laboratory tests and physical examinations unobtainable. The group of patients in our study who went from face-to-face to telemedicine may have decreased their adherence and methotrexate use due to the conditions contemplated by Mancuso et al Note that there was a significant increase in self-care among patients who had their first visit (TR model) or the entire follow-up in the face-to-face model, probably related to the fear of contracting the infection due to leaving their home.…”
Section: Discussionmentioning
confidence: 99%
“…The enrollment period coincided with peak mortality rates due to the virus in New York City in April 2020. Patients were interviewed in depth with open-ended questions and standard surveys, and a rich tableau of the pandemic's adverse effects on personal, social, professional, emotional, and physical health was assembled 9–12 . Our plan was to track the clinical and personal impact of the unfolding pandemic longitudinally, and follow-up with patients at the time when a vaccine became available.…”
mentioning
confidence: 99%